Mites associated with the cultivation of strawberries Fragaria x ananassa Duchesne (Weston) in Pamplona, Norte de Santander (Revista Sistemas de Producción Agroecológicos, 2026)
The cultivation of Fragaria x ananassa Duchesne (Weston) strawberries is an important economic activity in the villages near the town center of Pamplona, Norte de Santander. Agronomic management of the crop is essential to ensure its quality and longevity. Tetranychus urticae Koch is considered the main pest of strawberries due to its high reproductive capacity in a short period of time and the damage it causes by reducing the plant’s photosynthetic capacity. Control of this pest is basically chemical. However, the availability of chemical molecules is limited, leading to their frequent and excessive use, and to the probable tolerance and onset of resistance processes. The present study sought to identify the mites associated with strawberry cultivation in Pamplona. Leaves with symptoms of T. urticae attack were collected in six different production areas over a period of six weeks. The collected specimens were mounted on microscopy slides in Hoyer’s medium and identified with the aid of a microscope and specialized keys. The presence of T. urticae was confirmed, and the pest species Phytonemus pallidus Banks and a potential field or post-harvest pest Tyrophagus putrescentiae Schrank and the predator Neoseiulus californicus were also recorded. The recording of a local population of the predator N. californicus opens up an opportunity for its breeding and release, which, together with campaigns on the importance of rational pesticide use, will make it possible to generate a more sustainable product with added value, increasing the income and quality of life of producers.
Keywords: Biological control; Natural enemies; Neoseiulus californicus; Phytonemus pallidus; Sustainability